ANALISIS SEKTOR EKONOMI UNGGULAN DI PROVINSI MALUKU UTARA - Marisa Diana; Dwi Susilowati; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2017)
This study entitled "Analysis Of The Leading Economic Sectors in North Maluku Province" aims to analyze the leading sector and non- leading sector, identifying the comparison and changes in the sector of economic growth in North Maluku Province 2010-2015. Analysis method use Lacotion Quotient (LQ),Growth Ratio Model and Shift Share. The result of LQ analysis of Ternate City has the highest sector among other regencies or city in North Maluku Province , the leading sectors in North Maluku Province are agriculture and construction sectors. The result of MRP analysis on potential economic sector in economic growth either at district or city and provincial trade sector, car and motorcycle repair, construction sector and electricity and gas sector. The result of Shift Share analysis indicates that the growth of economic sector in North Maluku Province has a positive effect on the growth of economic sector in North Halmahera and South Halmahera Regency. Keywords: Leading Sectors, Growth Ratio, Economic Growth.